Port Jackson Shark Growth Is Sensitive to Temperature Change - Izzo, Christopher; Gillanders, Bronwyn May (Frontiers in Marine Science, 2020)
Climatic effects on the growth of apex marine predators – such as sharks – are poorly understood; moreover, shifts in shark growth are primarily attributed to fishing pressure. This paucity of information impedes management and conservation planning for these taxa. Using vertebral increment patterning as a proxy of somatic growth, this study reconstructed mean growth of the philopatric and demersal Heterodontus portusjacksoni population from Gulf St Vincent (South Australia). A biochronology of shark growth spanning 1996 to 2010 was developed using linear mixed effect models. The biochronology showed considerable year-to-year deviations in growth that were significantly and negatively correlated with mean sea surface temperatures during the species’ breeding season (July to November). These findings are consistent with mesocosm experiments and support the influence of changing climates on shark growth; particularly in an inshore, demersal and highly philopatric shark species. It is likely that the effects of environmental variation occur in a species-specific manner, governed by life history strategies and ecological requirements. In this manner, life history traits might aid in estimating species vulnerability to climate change.